Phylogenomics of palynophagous pine cone weevils (Coleoptera: Cimberididae) recovers the monophyly of Cimberidini and Doydirhynchini and reveals the paraphyly of Cimberis - Duane D. MCKENNA; Brian D. FARRELL; Adriana E. MARVALDI; Rolf G. OBERPRIELER; Xuankun LI (European Journal of Entomology, 2024)
The beetle family Cimberididae (pine cone weevils) consists of one extant subfamily, Cimberidinae, and two tribes, Cimberidini and Doydirhynchini, both limited in distribution to the Northern Hemisphere. Cimberidini comprise the genera Acromacer Kuschel, Cimberis Gozis and Pityomacer Kuschel and Doydirhynchini the genera Doydirhynchus Dejean and Lecontellus Kuschel. The larvae and adults of all known extant Cimberididae are palynophagous (pollen-feeding) in the male strobili of conifers of the genus Pinus (L.) (Pinaceae). We reconstructed the phylogeny of Cimberididae using data from 420 nuclear genes obtained via anchored hybrid enrichment. Our taxon sample included six species representing all described extant genera of Cimberididae except Pityomacer, which was unavailable for study. Most relationships in the resulting maximum-likelihood trees based on nucleotide and amino-acid sequence data were recovered with maximal bootstrap support. Both trees showed a monophyletic family Cimberididae, containing two clades corresponding to the tribes Cimberidini and Doydirhynchini. In Cimberidini, Cimberis was rendered paraphyletic by Acromacer bombifrons (LeConte). Notably, the internal and terminal branches of Cimberidini were very short compared to other parts of the tree. Generic relationships are discussed according to the phylogenetic results. To make the genus Cimberis monophyletic, we synonymize the names Cimberis Gozis, 1881 and Acromacer Kuschel, 1989 (syn. n.) and re-establish the combination Cimberis bombifrons (LeConte, 1876), proposed by Kuschel (1959). This study provides the first molecular phylogenetic hypothesis for the palynophagous weevil family Cimberididae.